Assessing youth empowerment and co‐design to advance Pasifika health: a qualitative research study in New Zealand - Danielle Prapaveissis; Akerere Henry; Elizabeth Okiakama; Tevita Funaki; Gavin Faeamani; Jennifer Masaga; Blakely Brown; Keawe Kaholokula; Claire Ing; Anna Matheson; Jemaima Tiatia‐Seath; Max Schleser; et al. (Elsevier, 2022)
Abstract Objectives: The Pasifika Prediabetes Youth Empowerment Programme (PPYEP) was a community‐based research project that aimed to investigate empowerment and co‐design modules to build the capacity of Pasifika youth to develop community interventions for preventing prediabetes. Methods: This paper reports findings from a formative evaluation process of the programme using thematic analysis. It emphasises the adoption, perceptions and application of empowerment and co‐design based on the youth and community providers' experiences. Results: We found that the programme fostered a safe space, increased youth's knowledge about health and healthy lifestyles, developed their leadership and social change capacities, and provided a tool to develop and refine culturally centred prediabetes‐prevention programmes. These themes emerged non‐linearly and synergistically throughout the programme. Conclusions: Our research emphasises that empowerment and co‐design are complementary in building youth capacity in community‐based partnerships in health promotion. Implications for public health: Empowerment and co‐design are effective tools to develop and implement culturally tailored health promotion programmes for Pasifika peoples. Future research is needed to explore the programme within different Pasifika contexts, health issues and Indigenous groups.